Insights into Biomechanical and Proteomic Characteristics of Small Diameter Vascular Grafts Utilizing the Human Umbilical Artery - Panagiotis Mallis; Dimitrios P. Sokolis; Manousos Makridakis; Jerome Zoidakis; Athanasios D. Velentzas; Michalis Katsimpoulas; Antonia Vlahou; Alkiviadis Kostakis; Catherine Stavropoulos-Giokas; Efstathios Michalopoulos (Biomedicines, 2020)
The gold standard vascular substitutes, used in cardiovascular surgery, are the Dacron or expanded polytetrafluoroethylene (ePTFE)-derived grafts. However, major adverse reactions accompany their use. For this purpose, decellularized human umbilical arteries (hUAs) may be proven as a significant source for the development of small diameter conduits. The aim of this study was the evaluation of a decellularization protocol in hUAs. To study the effect of the decellularization to the hUAs, histological analysis was performed. Then, native and decellularized hUAs were biochemically and biomechanically evaluated. Finally, broad proteomic analysis was applied. Histological analysis revealed the successful decellularization of the hUAs. Furthermore, a great amount of DNA was removed from the decellularized hUAs. Biomechanical analysis revealed statistically significant differences in longitudinal direction only in maximum stress (p < 0.013) and strain (p < 0.001). On the contrary, all parameters tested for circumferential direction exhibited significant differences (p < 0.05). Proteomic analysis showed the preservation of the extracellular matrix and cytoskeletal proteins in both groups. Proteomic data are available via ProteomeXchange with identifier PXD020187. The above results indicated that hUAs were efficiently decellularized. The tissue function properties of these conduits were well retained, making them ideal candidates for the development of small diameter vascular grafts.